Educational innovations beyond technology nurturing leadership and establishing learning organizations - Law, Nancy (Springer, 2011)
The text explores the concept of innovation, and analyses and compares the different dimensions of innovation found in the case studies presented. It also discusses the anticipated changes to the education profession at a system level, in the coming decade.